(untitled) (LACCEI, 2024)
This project’s main objective is to propose an operating model based on knowledge management for administrative processes in educational institutions. With this in mind, a population made up of six (6) people who make up the administrative staff of the study control department of the Haydeé Calles de Medina Educational Unit in the city of Coro in the state of Falcón was taken. The data collection techniques will be based on direct observation and a questionnaire-type survey, the methodology to be used is the one proposed by Nonaka and Takeuchi, this proposal will seek to increase the quality and efficiency in the management of the services it performs, allowing the integration of the different processes and in general thereby changing the way in which the institution currently operates, helping in its productive activities, facilitating administrative management, reducing the time spent on procedures and consultations, as well as a higher quality in the services provided. To achieve the proposed objectives, 8 phases will be implemented that will allow progress with the object of study.